The Effort of the General Election Commission of Mojokerto Regency to Improve Community Participation in the 2020 General Local Election during the Covid-19 Pandemic - Adi, Dikrilia A. Rizki Ertika; Said, M. Mas’ud; Kurniati, Rini Rahayu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study examines the effort of and the barriers faced by the General Election Commission (Komisi Pemilihan Umum - KPU) of Mojokerto Regency to improve community participation in the 2020 General Local Election (Pemilihan Kepala Daerah - PILKADA) during the Covid-19 pandemic. This study was qualitative to explore comprehensively the phenomenon under study. Data were collected through interviews, observations, and document analysis. Data were analyzed through data reduction, display, and conclusion drawing or verification. Findings confirmed that the pandemic became a new challenge for PILKADA 2020. KPU Mojokerto tried to tackle the challenge through socialization, partnerships with relevant actors, and providing better information access through social and electronic media. Other challenges included the need for knowledge of the local community on the importance of the election, low trust of the community to candidates, money politics, and low interest of the local community in the election process. It is recommended that the KPU Mojokerto improve the awareness of the local community on the importance of their votes in the election, strengthen partnerships with relevant actors, and disseminate information through various channels.